1929
DOI: 10.1084/jem.49.3.361
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Lymphatic Tissue

Abstract: In 87 rabbits, some of which received intravenously at various intervals small, and some large, doses of killed staphylococci, the following findings were obtained. 1. There occurred a hyperplasia of lymph nodes, spleen and thymus, that is to say, a status thymicolymphaticus. This phenomenon is explained as due to immediate local irritation caused by bacteria and their products and by certain "toxins" partly of exogenous, partly of endogenous, origin. 2. The lymphocytosis which ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1930
1930
1973
1973

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…of antigen in saline produced mesenchymal reactions in the lungs, cloudy swelling and sometimes necrosis of the liver, and other systemic changes. The mesenchymal reactions in the lungs were not unlike those which Rist (12) observed in experiments with killed tubercle bacilli in paraffin oil; but while Rist believed that they were tuberculous in nature, we find that they are nonspecific; they are identical with the mesenchymal reactions following the injection of killed staphylococci and other bacteria described earlier by Ehrich and coworkers (13)(14)(15). The nature of these reactions is not entirely clear.…”
Section: Antigen In Oilsupporting
confidence: 54%
“…of antigen in saline produced mesenchymal reactions in the lungs, cloudy swelling and sometimes necrosis of the liver, and other systemic changes. The mesenchymal reactions in the lungs were not unlike those which Rist (12) observed in experiments with killed tubercle bacilli in paraffin oil; but while Rist believed that they were tuberculous in nature, we find that they are nonspecific; they are identical with the mesenchymal reactions following the injection of killed staphylococci and other bacteria described earlier by Ehrich and coworkers (13)(14)(15). The nature of these reactions is not entirely clear.…”
Section: Antigen In Oilsupporting
confidence: 54%
“…Scheyer (22) earlier had correlated the amount of proliferation of reticulo-endothelial elements in various sites with the dinical course in puerperal sepsis, and found that the presence of focal reaction indicated a certain degree of resistance to the infection. Intense mononuclear cellular proliferation was observed by Ehrich (23) and by Nye and Parker (24) in animals following prolonged intravenous injection of bacteria; and the latter described similar lesions after the injection of certain colloids.…”
Section: Discussionmentioning
confidence: 61%
“…Ehrich (5) injected staphylococcus of low virulence subcutaneously and found a regional hyperplasia of the lymph nodes and some increase in lymphocytes in the peripheral blood. Injecting killed staphylococci intravenously (6), he obtained an increase in the number of circulating lymphocytes, which reached a maximum at about the 10th and 14th day, and then decreased to normal, although the injections were continued. Hyperplasia of spleen and lymph nodes was observed.…”
mentioning
confidence: 98%